A Formal Overview of Application Sandbox in Android and iOS with the Need to Secure Sandbox Against Increasing Number of Malware Attack - Philip, Jithu; Raju, Merin (Indian Journal of Computer Science, 2019)
Android and iOS are the most popular and commonly used mobile operating systems in the world. The increase in the usage share of these along with the extensive use of internet in smartphones and tablets lead to security threats being spread more frequently than expected for both. This document describes one of the security mechanisms used from earlier days of operating systems called Sandbox or Application Sandbox. The document also specifies details regarding how Application Sandbox is implemented in Android and iOS along with the common causes for malware attacks on both and an analysis about the common vulnerabilities and exposures reported on both the platforms. The major issue that the document focuses on is to make the users aware of the need to make use of protection mechanisms like Sandbox effectively to reduce the number of malware attacks.